(untitled) (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
This study examines the representation of space in the Territory Planning (PDT) in the activity of transport with a focus space in Latin America and Brazil, as is assessed by six Strategic Environmental Assessment (SEA) reports. Among these six, two refer to Brazil, two in Bolivia, one in Chile and Peru. The objective of this work is to evaluate the representations of geographic space (GS) in Strategic Environmental Assessments Plans Planning of Transport Activity. This is justified because the concept of territorial planning is changing in his speech, in its meaning, which introduces new challenges.